AB0514 PARATHORMONE BUT NOT VITAMIN D SERUM LEVELS ARE ASSOCIATED WITH SUBCLINICAL ATHEROSCLEROSIS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Giannelou, Mayra; Stamouli, Aikaterini; Antypa, Eleni; Moutsopoulos, Haralampos M.; Mavragani, Clio
Abstract : Background: Growing evidence supports a link between alterations in bone metabolism and cardiovascular (CV) disease in both general and autoimmune populations. Objectives: In the current study we aimed to explore whether vitamin D deficiency and/or increased parathormone (PTH) levels, as well as impairment of bone mass density, influence CV risk in patients with systemic lupus erythematosus (SLE). Methods: 138 consecutive SLE patients were enrolled in the study. Clinical features, hematological, serological and immunological profile, as well as therapeutic regimens was recorded in all patients. Classical CV and osteoporosis risk factors were assessed in all participants. Intima-medial thickness scores (IMT) and carotid and/or femoral (C/F) plaque formation were evaluated by ultrasound. Assessment of bone mineral density (BMD) and asymptomatic osteoporotic fractures was also performed by dual X-ray absorptiometry and lateral thoracic and/or lumbar spine X-rays, respectively. Univariate and multivariate models were implemented for statistical analysis. Results: PTH -but not 25(OH)vitamin D3- serum levels were found to be increased in lupus patients with subclinical atherosclerosis (plaque formation and/or arterial wall thickening) compared to those without (51.1±27.7 vs 37.4±18.4 pg/ml, p= 0.003 and 54±32.7 vs 40±18.3 pg/ml, p= 0.02, respectively). Abnormal PTH serum concentrations (>65 pg/ml) in SLE patients was identified as a risk factor for both plaque formation and high IMT scores (>0.9mm) [OR 95% (CI): 8.2 (1.8-37.4) and OR 95% (CI): 3.9 (1.3-11.8), respectively]. High PTH levels were found to be associated with low 25(OH)vitaminD3 levels, advanced age and increased triglycerides in the lupus cohort. Moreover, SLE patients with plaque formation exhibited increased rates of osteoporosis (based on WHO classification) compared to those without [19.5% vs 5.3%, p= 0.017, OR 95% (CI): 4.4 (1.2-15.9)]. Finally, an inverse correlation between femoral neck BMD values and total IMT scores was observed (r:-0.42, p=0.008). Conclusion: Subclinical atherosclerosis in patients with lupus is associated with increased serum PTH levels and reduced bone mass density. These findings further support the presence of shared etiopathogenetic mechanisms between atherogenesis and altered bone metabolism. Disclosure of Interests: None declared